Decision Support System for Premises Assessment of PT. Bank Perkreditan Rakyat NBP 33 with TOPSIS Method - Sihaloho, Risma Veronika; Purba, Megaria (Journal of Data Science, Technology, and Artificial Intelligence, 2024)
The premises assessment at PT. BPR NBP 33 still relies on a manual evaluation based solely on the highest number of votes, without considering premises criteria. The method employed is the TOPSIS method. This method has advantages such as a simple and easy-to-understand concept, efficient computation, and the ability to measure the relative performance of decision alternatives in a simple mathematical form. There are 5 (five) criteria used as measurement tools for premises assessment, including banking hall equipment, room comfort, toilets, parking facilities, and transaction facilities. Four (4) alternatives are considered. Based on the ranking results of the alternatives, the branch office with the best premises assessment is KCP. Batang Kuis, with a final score of 0.84440, securing the top ranking. This decision support system is developed using PHP programming language and MySQL database.